Amelioration of cyclophosphamide-induced DNA damage, oxidative stress, and hepato- and neurotoxicity by Piper longum extract in rats: The role of γH2AX and 8-OHdG - Yadav, Vaishali; Krishnan, Anuja; Zahiruddin, Sultan; Ahmad, Sayeed; Vohora, Divya (Frontiers in Pharmacology, 2023)
Background: The identification of genoprotectants is a promising strategy for improving human health. Piper longum has drawn scientific attention because of its diverse biological effects and traditional utilization. The current investigation aims to evaluate the genome-stabilizing potential of Piper longum against cyclophosphamide-associated genotoxicity. Methods: We adopted a funnel screening with a three-tier evaluation approach, where Piper longum was investigated in an acellular medium, peripheral blood lymphocytes, and a rodent model. The genoprotective action of the Piper longum extract was initially performed with plasmid pBluescript SK(-) DNA. Furthermore, the extract and various fractions were screened against cyclophosphamide-induced genotoxicity using a cytokinesis-block micronucleus assay and a chromosomal aberration assay in human peripheral blood lymphocytes. The genome-stabilizing action of the extract and potent (hexane) fraction was further confirmed in vivo in Wistar albino rats by evaluating them using mammalian erythrocyte micronucleus tests, DNA fragmentation, oxidative stress markers, 8-hydroxy-2-deoxyguanosine (8-OHdG), γH2AX, and histopathological lesions in the liver and hippocampus. Additionally, acute and sub-acute toxicity studies were conducted following the Organization for Economic Co-operation and Development (OECD) guidelines for rats. Furthermore, the extract was quantified and characterized by high-performance thin-layer chromatography (HPTLC), ultra-high performance liquid chromatography–mass spectroscopy (UPLC-MS), and gas chromatography–mass spectrometry (GC-MS). Results: The Piper longum ethanol extract was shown to protect plasmid pBluescript SK(-) DNA against H2O2-induced strand breaks. In human lymphocytes, the extract and hexane fraction showed a reduction in micronucleus formation (p < 0.001) and chromosomal aberrations (p < 0.01) against cyclophosphamide. Furthermore, the extract and fraction treatment, when administered at 200 mg/kg for 28 days in Wistar rats, restored cyclophosphamide-induced genomic instability by reducing micronucleus formation and DNA fragmentation; restoring redox homeostasis; decreasing 8-OHdG, a hallmark of oxidative DNA damage; reducing γH2AX, a DNA double-strand break (DSB) marker; and preserving the liver and hippocampus against histopathological lesions. The extract and fraction revealed no signs of systemic toxicity at the used doses. Piperine and piperlongumine are the major alkaloids quantified along with the presence of flavonoids in the ethanol extract and the presence of fatty acids and terpenoids in the hexane fraction of Piper longum. Conclusion: Our investigation confirms the genoprotective action of Piper longum by reducing cyclophosphamide-associated cytogenotoxicity, oxidative stress, hepato- and neurotoxicity, oxidative DNA damage, and DNA double-strand breaks. The outcomes are critical for mitigating the genotoxic effects of chemotherapy recipients, requiring further attention.